Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

The role of solvent in lignin hydrothermal liquefaction: its influence on conversion and phenolic monomer selectivity - Dong-Can Lv; Meng-Ru Chen; Yue-Yuan Ye; Duo Wang; Zhi-Min Wang; Yun-Quan Liu (Fuel, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Doping-engineered nanosystem for enhancing the antibacterial efficiency of scaffolds through synergistic aSDT and CDT - Wenjie Ma; Ru Jia; Patiguli Aihemaiti; Houfeng Jiang; Lanlan Dong; Wurikaixi Aiyiti; Cijun Shuai; Chongxian He (Chemical Engineering Journal, 2026)

Synergistic photodynamic and photothermal antibacterial therapy enabled by BSCN heterojunction in PEEK bone implants - Ru Jia; Wenjie Ma; Wurikaixi Aiyiti; Houfeng Jiang; Patiguli Aihemaiti; Lanlan Dong; Cijun Shuai (Chemical Engineering Journal, 2026)

Close-to-nature management alters litterfall production and nutrient return in Chinese fir (Cunninghamia lanceolata) plantations across Southern China - Shu-meng Wei; Xiang-teng Chen; Ru-zhen Jiao; Xiong-qing Zhang; Yu-hong Dong (European Journal of Forest Research, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

DLP printed hydrogel sensors with tunable sensitivity via a molecular-structural co-design - Lanlan Dong; Quankun Jiao; Ru Jia; Jing Wang; Wurikaixi Aiyiti; Cijun Shuai (Chemical Engineering Journal, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Correction to: Engineered Alzheimer Organoids Validate the Link Between Intracellular and Soluble p-Tau Biomarkers and Highlight the Contribution of Astrocytic Tau - Ru Zhang; Xiaoxu Dong; Gang Pei; Shichao Huang (Neuroscience Bulletin, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Rethinking crustacean shell waste valorization: from environmental burden to microbial platform for sustainable bioproducts - Ru-Li He; Dong-Feng Liu (ENGINEERING Environment, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Metabolic-Epigenetic-Immune axis in Ischemic Stroke: Lactate-derived Lactylation as a Key Regulator - Xin-Yu Dong; Xin-Ru Pan; Xiao-Shuang Feng; Jia-Xin Xie; Xiao-Yi Xiong (Metabolic Brain Disease, 2026)

Engineered Alzheimer Organoids Validate the Link Between Intracellular and Soluble p-Tau Biomarkers and Highlight the Contribution of Astrocytic Tau - Ru Zhang; Xiaoxu Dong; Gang Pei; Shichao Huang (Neuroscience Bulletin, 2026)

New fossil moths (Lepidoptera: Micropterigidae) in middle Cretaceous Kachin amber from Myanmar - Ning Han; Xin-Ru Luo; Jia-Jia Wang; Chungkun Shih; Wei-Ting Zhang; Dong Ren (Palaeoworld, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Humic acid facilitates microbial manganese oxidation-driven arsenic remediation in soil across a wide temperature range - Weiwei Zhai; Wenjin Zhang; Lingfeng Dong; Yulong Ru; Yao Xu; Zhanfei He; Daoyong Zhang; Xiangliang Pan (Journal of Environmental Management, 2026)

Impact of polysaccharide addition on the digestive properties of porcine bone soup:Based on the gastrointestinal tracts of adults and elderly - Meiqi Dang; Dongmei Zhang; Huilong Dong; Shanbai Xiong; Ru Liu; Tao Yin; Juan You (Food Research International, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

A microgel-microstructure synergistically enhanced flexible sensor via DLP 3D printing for wearable electronics - Xiangyu Liu; Lijun Dong; Yi Ru; Lanlan Dong; Wurikaixi Aiyiti; Cijun Shuai (Chemical Engineering Journal, 2026)

Tailoring hydrophilic channels size in multiblock poly(aryl alkyl) membranes for anion exchange membrane water electrolysis - Xuejiao Dong; Weiwei Luan; Yixiang Ma; Minglong He; Bin Wu; Jibin Miao; Ru Xia; Jiasheng Qian; Guangzu Wang; Qianqian Ge (Desalination, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

A dramatic drop in Nb solubility during fractional crystallization of carbonatites triggers Nb ore formation - Ya-Ting Xu; Ru-Cheng Wang; Xu-Dong Che; Fabrice Gaillard; Marion Louvel; Giada Iacono-Marziano; Johann Tuduri (Geochimica et Cosmochimica Acta, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Wide-area coastal deformation extraction using multi-path/frame InSAR: A case study of the Bohai Rim - Zhiqiang Gong; Mingsheng Liao; Jie Dong; Qianye Lan; Ru Wang; Shangjing Lai (Remote Sensing of Environment, 2025)

ZnCl2 activated biochar and chitosan composites for efficient adsorption of tetracycline pollution in sewage - Chi Ru; Xixi Lian; Dong Liang; Taoli Huhe; Rui Shan; Haoran Yuan; Yong Chen (Process Safety and Environmental Protection, 2025)

A single Drosophila Dscam1 genomic locus generates a vast repertoire of circRNAs facilitated by RNA pairing - Zedong Li; Bingbing Xu; Zhechao Wang; Wenjie Zhang; Jiayan Fu; Lili Wu; Nengcheng Bao; Jinpeng Xie; Ru Yan; Haiyang Dong; Yongfeng Jin (Insect Biochemistry and Molecular Biology, 2025)

Enhancing emulsion stability in pork bone soup: Exploring the synergistic effects of polysaccharides and high-pressure homogenization - Yajin Zhang; Dongmei Zhang; Huilong Dong; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (Food Chemistry, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Correction: The correlation of fibrinogen‑like protein‑1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

Alteration in conformation and emulsibility of lactoferrin-low methoxyl pectin complexes induced by non-covalent interactions with rosmarinic acid - Chuanrui Jiang; Fujun Liu; Yuxin He; Ru Zhao; Chao Dong; Tiehua Zhang; Cuina Wang (Food Chemistry, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

A scientific data-driven review of natural product genipin for disease therapy - Dong Xu; Tao Qiao; Kai Gao; Mei-Na Zhao; Wei Zhang; Xing-Ru Tao; Jing-Wen Wang (Phytochemistry Reviews, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Covalent binding of vitamin K3 photosensitizers to nanofibrous membranes for daylight-driven antimicrobial applications - Yibo Ru; Qingli Dong; Kexin Li; Xinyi Zhao; Lang Yan; Xiang Wang; Yangtai Liu; Yue Ma (Chemical Engineering Journal, 2025)

The effect of ligand regulation on mechanism of alkaline oxygen evolution reaction under industrial scale - Xin-Ru Li; Xue-Jun Zhai; Hao-Zheng Liu; Xin Wen; Yanbin Qi; Chen Zhang; Guodong Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Facile blending modification and high-voltage activation strategy enabled long-cycle performance of single crystalline nickel-rich cathode materials - Honglei Liu; Yong Wu; Deli Li; Chengzhi Hu; Lei Zou; Tao Xu; Qiang Wang; Weijian Tang; Dongxu Liu; Ranlin Dong; Ru Song; Zeheng Yang; et al. (Chemical Engineering Journal, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

The heading stage: A critical period for schwertmannite in reducing arsenic accumulation in rice (Oryza sativa L.) - Yan Dong; Jiawei Yang; Ru Wang; Bo Zhou; Mingjiang Zhang; Guanyu Zheng; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Systematic review of natural coumarins in plants (2019–2024): Chemical structures and pharmacological activities - Ze-Dong Nan; Ying Shang; Yi-Dong Zhu; Hui Zhang; Ru-Ru Sun; Jing-Jing Tian; Zhi-Bo Jiang; Xiao-Li Ma; Changcai Bai (Phytochemistry, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Enhancement mechanism of residue Gd (III)-induced in anaerobic ammonia oxidation for nitrogen removal from rare earth tailings leachate - Xiangyi Deng; Ting Zeng; Shengnan Huang; Chunqiao Xiao; Liu Liu; Wanqiang Dong; Zhenyue Zhang; Ru’an Chi (Journal of Environmental Chemical Engineering, 2025)

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Novel screening of molecular markers reveals genetic basis for heterosis in hybrids from red crucian carp and white crucian carp - He Zhang; Ru Li; Yun Zeng; Jun Wang; Zhizhi Liu; Yi Zhou; Chenghui Wang; Dong Liu (Aquaculture, 2025)

Factors Influencing Knowledge-Action Gap in Patients With Metabolic Dysfunction-Associated Fatty Liver Disease: A Qualitative Study - Qing Guan; Rui Dong; Mengting Zhang; Dongchun Chang; Ru Zhang; Yunqi Wang; Wei Zhang; Jie Wang (Journal of Nutrition Education and Behavior, 2025)

Structural and electronic regulation of transition metal borides: from controllable synthesis to industrial alkaline water splitting - Na Xu; Xin-Ru Li; Denghao Ouyang; Guodong Li; Shijian Cheng; Zhongmin Tang; Yong-Ming Chai; Bin Dong (Fuel, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Dynamic responses of the inter-microbial synergism and thermodynamic conditions attribute to the inhibition-and-relief effects of chitosan towards anaerobic digestion - Ru Fang; Xueting Wang; Zhibang Han; Ruirui Pang; Dong Wu; Jun Tai; Chuang Ouyang; Min Zhan; Hyunook Kim; Bing Xie; Yinglong Su (Water Research, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

Formation and kinetic analysis of AGEs in Pacific white shrimp during frying - Runlin Wu; Xia Mou; Shiyuan Dong; Ramy M. Khoder; Shanbai Xiong; Ru Liu (Food Chemistry, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Abnormal Changes of IL3/IL3R and Its Downstream Signaling Pathways in the Prion-Infected Cell Line and in the Brains of Scrapie-Infected Rodents - Xiao-Xi Jia; Cao Chen; Chao Hu; Zhi-Yue Chao; Wei-Wei Zhang; Yue-Zhang Wu; Qin Fan; Ru-Han A; Xin Liu; Kang Xiao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2024)

Response of anammox to organics with different degradation characteristics and exposure time: Performance, sludge characteristics and bacterial community - Shuai Zhang; Long-Yun Lai; Tian-Xiang Wang; Wei-Lei Jin; Ru-Ru Yi; Dong-Zhi Chen; Ren-cun Jin; Guang-feng Yang (Science of The Total Environment, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Regulating N-doped biochar with Fe-Mo heterojunctions as cathode in long-life zinc-air battery - Xiao-ru Meng; Shuai Gao; Nianxi Liu; Pei-dong Wu; Zhen Fang (Chemical Engineering Journal, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Mechanism of Efferocytosis in Determining Ischaemic Stroke Resolution—Diving into Microglia/Macrophage Functions and Therapeutic Modality - Xiao-Di Xie; Shan-Shan Dong; Ru-Juan Liu; Liu-Liu Shi; Ting Zhu (Molecular Neurobiology, 2024)

Integrative multi-omics analysis reveals the underlying toxicological mechanisms of enrofloxacin on the growth of wheat seedling roots - Xiaojun Wu; Xiangdong Chen; Dazhong Zhang; Xigui Hu; Weihua Ding; Yuquan Wang; Gan Li; Na Dong; Haiyan Hu; Tiezhu Hu; Zhengang Ru (Journal of Hazardous Materials, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Direct evidence from STXM analysis of enhanced oxygen storage capacity in ceria through the addition of Cu and Mg: Correlation of HT-WGS reaction performance - Ru-Ri Lee; Dong-Hyun Kim; Kyung-Won Jeon; I-Jeong Jeon; Chang-Hyeon Kim; Alexander S. Ditter; David A. Shapiro; Matthew A. Marcus; Hendrik Ohldag; Karen C. Bustillo; Young sang Yu; Won-Jun Jang; et al. (Chemical Engineering Journal, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Ecological restoration largely alleviates livestock grazing pressure in a montane grassland - Xiao-lian Qi; Hao-jie Xu; Ru-yu Teng; Tian Chen; Xu-dong Wang (Journal of Cleaner Production, 2024)

Determination of operation parameters for magnesium-air fuel cell to recover nitrogen and phosphorus from wastewater - Xingze Li; Sizhuo Wan; Tingting Dong; Zhiguo Zhao; Ru Wang (Journal of Environmental Management, 2024)

Estimation of linezolid exposure in patients with hepatic impairment using machine learning based on a population pharmacokinetic model - Ru Liao; Lihong Chen; Xiaoliang Cheng; Houli Li; Taotao Wang; Yalin Dong; Haiyan Dong (European Journal of Clinical Pharmacology, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

Chemical constituents with antioxidant activity from the branches and leaves of Hultholia mimosoides - Ru Feng; Jia-Xin Xu; Xiao-Yi Luan; Xiao-Ning Wang; Tao Shen; Dong-Mei Ren; Xiao-Ling Wang (Phytochemistry, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Sex-specific impacts of thimerosal on the behaviors and brain monoaminergic systems in zebrafish (Danio rerio) - Xuchun Qiu; Zhen Su; Jiarui Gao; Yiming Cui; Kejun Dong; Kun Chen; Ru-Jin Zhao; Songmei Wang; Tao Wu; Yanhong Shi (Aquatic Toxicology, 2024)

Potential use of maize–peanut intercropping to adapt to drought and nitrogen–shortage impacts - Fei Han; Shuqing Guo; Muhammad Asad Naseer; Ru Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Dong Yang; XiaoLi Chen; Xiaolong Ren (Plant and Soil, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Analytical method for evaluating the tensioned membrane effect in the geosynthetic-reinforced unsaturated embankment soil subjected to localized sinkholes - Hao-ru Zhang; Xiao-qiang Dong; Xi-dong Zhang; Ming-xing Xie (European Journal of Environmental and Civil Engineering, 2024)

Comprehensive impacts of the presence of proton exchange membrane on the efficiency of Mg-air fuel cell to remove nutrients and recover struvite - Tingting Dong; Xingze Li; Zhiguo Zhao; Ru Wang (Journal of Water Process Engineering, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Edible antimicrobial yeast-based coating with basil essential oil for enhanced food safety - Yibo Ru; Yuqi Zhu; Xiang Wang; Qingli Dong; Yue Ma (Innovative Food Science & Emerging Technologies, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

On the origin of selectivity in extracting and separating lanthanide ions by alkyl-nitrilotriacetamide - Yu-Chang Hou; Juan Wang; Yuan-Ru Guo; Song-Dong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Risk Assessment for Recreational Activities in the Coastal Ocean - Hui-Chieh Chuang; Dong-Jiing Doong; Chung-Ru Ho; Ya-Hui Ho (Journal of Marine Science and Engineering, 2024)
Ocean recreational activities (ORAs), including swimming, surfing, diving, paddleboarding, etc., in global marine areas are becoming increasingly popular. However, there are potential risks in coastal ocean environments. This study aims to establish a framework for assessing the risk according to the joint hazard and vulnerability levels of the ORA environment. Important factors include meteo-ocean conditions, geographic features, biological and chemical characteristics, and records of historical accidents, as well as social, environmental and tourist perceptions. The fuzzy Delphi method (FDM) is used to screen the representative factors, followed by using the analytical hierarchy process (AHP) to determine the weight of each factor. The results show that 9 hazard factors and 12 vulnerability factors are dominant. The framework is applied to 307 beaches in Taiwan, and 8% of them are categorized as very high risk and 13% as very low risk for ORAs. A risk map that displays the hazard, vulnerability, and overall risk levels is presented to tourists to provide quick access to risk information.

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Can Antibiotic Resistance Genes in Household Food Waste be Reduced by Earthworm Vermicomposting? Underpinning Mechanisms and Strategies - Ru Fang; Xiaojing Liu; Zhipeng Zheng; Baoyi Lv; Jie Wang; Yinglong Su; Bing Xie; Dong Wu (Reviews of Environmental Contamination and Toxicology, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

From air to airway: Dynamics and risk of inhalable bacteria in municipal solid waste treatment systems - Ru Fang; Tian Chen; Zhibang Han; Wenhui Ji; Yudan Bai; Zhipeng Zheng; Yinglong Su; Ling Jin; Bing Xie; Dong Wu (Journal of Hazardous Materials, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Comprehensive assessment of metals and organic pollutants in pelagic fishing port sediments - Chih-Feng Chen; Shu-Hui Lee; Yun-Ru Ju; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Effects of exposure to chlorinated paraffins on human health: A scoping review - Jing-Wen Huang; Ya-Ying Bai; Mohammed Zeeshan; Ru-Qing Liu; Guang-Hui Dong (Science of The Total Environment, 2023)

Lycopene-loaded emulsions stabilized by whey protein covalently modified with pectin or/and chlorogenic acid: Enhanced physicochemical stability and reduced bio-accessibility - Yuanyuan Zhang; Tiehua Zhang; Chao Dong; Ru Zhao; Xiaoge Zhang; Cuina Wang (Food Chemistry, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

CAT Interruption as a Protective Factor in Chinese Patients with Spinocerebellar Ataxia Type 1 - Ya-Ru Shao; Jin-Yang Yu; Yin Ma; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2023)

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

A novel pollution index to assess the metal bioavailability and ecological risks in sediments - Chih-Feng Chen; Yee Cheng Lim; Yun-Ru Ju; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Nanoplastics induce more severe multigenerational life-history trait changes and metabolic responses in marine rotifer Brachionus plicatilis: Comparison with microplastics - Xuan Li; Lin Lu; Shaoguo Ru; Junho Eom; Dong Wang; Samreen; Jun Wang (Journal of Hazardous Materials, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Viewing landfill-borne antibiotic resistance genes through the kaleidoscope of “One Health”: Essential legacies and research needs from the environmental dimension - Dong Wu; Ru Fang; Bing Xie (Current Opinion in Environmental Science & Health, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Temporal dynamics of soil bacterial network regulate soil resistomes - Qian Xiang; Dong Zhu; Min Qiao; Xiao‐Ru Yang; Gang Li; Qing‐Lin Chen; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Soil bacteria are diverse and form complicated ecological networks through various microbial interactions, which play important roles in soil multi‐functionality. However, the seasonal effects on the bacterial network, especially the relationship between bacterial network topological features and soil resistomes remains underexplored, which impedes our ability to unveil the mechanisms of the temporal‐dynamics of antibiotic resistance genes (ARGs). Here, a field investigation was conducted across four seasons at the watershed scale. We observed significant seasonal variation in bacterial networks, with lower complexity and stability in autumn, and a wider bacterial community niche in summer. Similar to bacterial communities, the co‐occurrence networks among ARGs also shift with seasonal change, particularly with respect to the topological features of the node degree, which on average was higher in summer than in the other seasons. Furthermore, the nodes with higher betweenness, stress, degree, and closeness centrality in the bacterial network showed strong relationships with the 10 major classes of ARGs. These findings highlighted the changes in the topological properties of bacterial networks that could further alter antibiotic resistance in soil. Together, our results reveal the temporal dynamics of bacterial ecological networks at the watershed scale, and provide new insights into antibiotic resistance management under environmental changes.

Identification of mercury species in coal combustion by-products from power plants using thermal desorption-atomic fluorescence spectrometry on-line coupling system - Kai-Qiang He; Xiao-Ru Zhang; Yuan-Peng Li; Xue-Lei Duan; Yan Li; Yang-Hong Jiang; Xiao-Dong Yuan; Ke-Gang Zhang; Chun-Gang Yuan (Chemosphere, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Herbicide prometryn adversely affects the development and reproduction of Tigriopus japonicus by disturbing the ecdysone signal pathway and chitin metabolic pathway - Dong Wang; Guangxin Yang; Shaoguo Ru; Zhenzhong Zhang; Yuejiao Li; Jun Wang (Aquatic Toxicology, 2023)

A standard dose of linezolid puts patients with hepatic impairment at risk of overexposure - Ru Liao; Yalin Dong; Lihong Chen; Taotao Wang; Houli Li; Haiyan Dong (European Journal of Clinical Pharmacology, 2023)

Progressive Failure Characterization of Sandstone from Yingjinshan Area in Qinghai-Tibet Plateau - Xinzhong Wang; Heping Xie; Ru Zhang; Guangze Zhang; Zhengxuan Xu; Jianhui Deng; Dong Wang; Cunbao Li; Gan Feng; Zetian Zhang; Li Ren (Rock Mechanics and Rock Engineering, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Deciphering the Heterogeneity of Mitochondrial Functions During Hematopoietic Lineage Differentiation - Haoyue Liang; Shuxu Dong; Weichao Fu; Sen Zhang; Wenying Yu; Fang Dong; Baolin He; Jinhong Wang; Yingdai Gao; Yuan Zhou; Yongxin Ru (Stem Cell Reviews and Reports, 2022)

The correlation of fibrinogen-like protein-1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2022)
Background Fibrinogen-like-protein 1 (FGL1), a member of the fibrinogen-related protein (FREP) family, is a major ligand of the immune inhibitory receptor lymphocyte-activation gene 3 (LAG-3). While FGL1 is strongly implicated in the development and prognosis of a variety of diseases, its role in hepatocellular carcinoma (HCC) is still disputed. Therefore, the role of FGL1 expression in the progression and prognosis of HCC was investigated. Methods and results In the present study, bioinformatics analysis was first used to probe the expression profile of FGL1 in multiple malignant tumor tissues and paired normal tissues, and to explore the possible relationship between FGL1 and prognosis of HCC patients. Thereafter, the expression levels of FGL1 were determined and compared in human HCC cell lines, HCC tissues, peri-tumor tissues and normal liver tissues by western blot analysis. Furthermore, tissue microarrays were used to detect the expression of FGL1 through immunohistochemical staining and to verify whether the FGL1 expression level was associated with clinicopathological features and the prognosis of HCC patients. The results showed that FGL1 was downregulated significantly in most of the HCC cells lines and HCC tissues, corresponding to the results of the bioinformatics and western blot analyses. FGL1 expression level in HCC was found to be correlated to Edmondson grade and metastasis of the HCC. Additionally, high FGL1 expression was associated with better overall survival in HCC patients, suggesting that FGL1 could function as a tumor suppressor. Conclusions The expression level of FGL1 can be correlated with the progression and prognosis of HCC, suggesting its potential as a prognostic biomarker.

Energy characteristics and micro-cracking behaviors of deep slate rock under triaxial loadings - Anlin Zhang; Tao Feng; Liangwen Jiang; Dong Wang; Zhewei Wang; Ru Zhang; Gan Feng; Zhilong Zhang; Jianhui Deng; Li Ren (Acta Geophysica, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Impacts of nanoplastics on life-history traits of marine rotifer (Brachionus plicatilis) are recovered after being transferred to clean seawater - Dong Wang; Shaoguo Ru; Wei Zhang; Zhenzhong Zhang; Yuejiao Li; Lingchao Zhao; Lianxu Li; Jun Wang (Environmental Science and Pollution Research, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Succinic acid inhibits photosynthesis of Microcystis aeruginosa via damaging PSII oxygen-evolving complex and reaction center - Yi-dong Chen; Yuan Zhu; Jian-pan Xin; Chu Zhao; Ru-nan Tian (Environmental Science and Pollution Research, 2021)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Factors Associated with Intergenerational Instability of ATXN3 CAG Repeat and Genetic Anticipation in Chinese Patients with Spinocerebellar Ataxia Type 3 - Yi-Chu Du; Yin Ma; Ya-Ru Shao; Shi-Rui Gan; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

The Intruding Wolbachia Strain from the Moth Fails to Establish Itself in the Fruit Fly Due to Immune and Exclusion Reactions - Xin-Chao Liu; Yue-Ru Li; Bei Dong; Zheng-Xi Li (Current Microbiology, 2020)

Cenozoic Uplift of the Central Yunnan Fragment, Southwestern China, Revealed by Apatite (U-Th)/He Dating - Ke Wu; Youpu Dong; Jiaxin Duan; Xin Ru; Dongyue Zhang; Dan Wang (Journal of Earth Science, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Expression, purification, and characterization of a new Glucosyltransferase involved in the third step of O-antigen repeating-unit biosynthesis of Escherichia coli O152 - Chenying Dong; Diange Li; Ru Wang; Jian Chu; Zhongying Gong; Dawei Zhou (Glycoconjugate Journal, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Effect of metals on zooplankton abundance and distribution in the coast of southwestern Taiwan - Yun-Ru Ju; Wen-Tseng Lo; Chih-Feng Chen; Chiu-Wen Chen; Zhi-Ling Huang; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

The transcription factor MYB15 is essential for basal immunity (PTI) in Chinese wild grape - Yangyang Luo; Ru Bai; Jing Li; Weidong Yang; Ruixiang Li; Qingyang Wang; Guifang Zhao; Dong Duan (Planta, 2019)

Collembolans accelerate the dispersal of antibiotic resistance genes in the soil ecosystem - Dong Zhu; Hong-Tao Wang; Fei Zheng; Xiao-Ru Yang; Peter Christie; Yong-Guan Zhu (Soil Ecology Letters, 2019)

Spatial distribution and ecological risk assessment of sediment metals in a highly industrialized coastal zone southwestern Taiwan - Chiu-Wen Chen; Yee Cheng Lim; Chih-Feng Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Andrographolide impairs alpha-naphthylisothiocyanate-induced cholestatic liver injury in vivo - Lei Wang; Fei Cao; Li-li Zhu; Peng Liu; Yu-ru Shang; Wen-hui Liu; Xin Dong; Hai-dong Bao; Peng Gong; Zhong-yu Wang (Journal of Natural Medicines, 2019)

A specific allele of MYB14 in grapevine correlates with high stilbene inducibility triggered by Al3+ and UV-C radiation - Ru Bai; Yangyang Luo; Lixin Wang; Jing Li; Kerun Wu; Guifang Zhao; Dong Duan (Plant Cell Reports, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Novel combined method of biosorption and chemical precipitation for recovery of Pb2+ from wastewater - Jia-qi Tang; Jiang-bo Xi; Jun-xia Yu; Ru-an Chi; Jia-dong Chen (Environmental Science and Pollution Research, 2018)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Molecular cloning, antiserum preparation and expression analysis during head regeneration of $$\upalpha $$ α -crystallin type heat shock protein in Hydra vulgaris - Wen-Fang Dong; Hang Zhang; Ru-Meng Wang; Hong-Chun Pan (Journal of Genetics, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Calcium controls the formation of vacuoles from mitochondria to regulate microspore development in wheat - Dong Xiao Li; Hai Yan Hu; Gan Li; Zhen Gang Ru; Hui Qiao Tian (Plant Reproduction, 2017)

Selective adsorption and recycle of Cu2+ from aqueous solution by modified sugarcane bagasse under dynamic condition - Jia-dong Chen; Jun-xia Yu; Fen Wang; Jia-qi Tang; Yue-fei Zhang; Yuan-lai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2017)

Removal of Congo red from aqueous solution by adsorption onto different amine compounds modified sugarcane bagasse - Jun-xia Yu; Wan-li Xiong; Jing Zhu; Jia-dong Chen; Ru-an Chi (Clean Technologies and Environmental Policy, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Arabidopsis heat stress transcription factors A2 (HSFA2) and A3 (HSFA3) function in the same heat regulation pathway - Xiao-dong Li; Xiao-li Wang; Yi-Ming Cai; Jia-hai Wu; Ben-tian Mo; Er-ru Yu (Acta Physiologiae Plantarum, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Vertical profile, source apportionment, and toxicity of PAHs in sediment cores of a wharf near the coal-based steel refining industrial zone in Kaohsiung, Taiwan - Chih-Feng Chen; Chiu-Wen Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

CIC-3 chloride channel blockade protects mouse photoreceptor-derived 661W cells against ischemia-reperfusion-induced injury in vitro - Shi Wei Huang; Yuan Yin; Ya Juan Zheng; Ya Ru Dong (Molecular & Cellular Toxicology, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Genetic and serological characterization of chrysanthemum stem necrosis virus, a member of the genus Tospovirus - Pei-Ru Wu; Wan-Chu Chien; Mitsuru Okuda; Minoru Takeshita; Shyi-Dong Yeh; Yun-Chi Wang; Tsung-Chi Chen (Archives of Virology, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Culture of amelanotic melanocytes derived from human fetal hair follicles - Ru-zhi Zhang; Wen-yuan Zhu; Hong-zhou Li; Dong-zhang Xue; Cong-jun Jiang; Wan Li (In Vitro Cellular & Developmental Biology - Animal, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

Functional analysis of BT4 of Arabidopsis thaliana in resistance against Botrytis cinerea - Cong-Cong Hao; Jiao Jia; Zhan Chen; Ji-Hong Xing; Qiao-Yun Weng; Feng-Ru Wang; Jin-Gao Dong; Jian-Min Han (Australasian Plant Pathology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Overload training inhibits phagocytosis and ROS generation of peritoneal macrophages: role of IGF-1 and MGF - Weihua Xiao; Peijie Chen; Ru Wang; Jingmei Dong (European Journal of Applied Physiology, 2013)

Characterization and molecular mapping of RsrR, a resistant gene to maize head smut - W. H. Li; X. D. Xu; G. Li; L. Q. Guo; S. W. Wu; Y. Jiang; H. Y. Dong; M. L. Weng; D. M. Jin; J. Y. Wu; Z. G. Ru; B. Wang (Euphytica, 2012)
Maize head smut (MHS) caused by the fungi Sporisorium reilianum (Kühn) Landon and Fullerton ( S. reilianum ) is the most serious disease occurred in China recently. There are only a few reports concerning the genetics of this disease and the resistant gene of maize. In this paper a new dominant resistant gene to MHS caused by the pathogen Shenyang-1 of S. reilianum was discovered from a newly developed resistant inbred line ‘R24’ and was named RsrR. RsrR gene was molecular tagged and mapped on the long arm of maize chromosome 1 via simple sequence repeat-bulked segregant analysis (SSR-BSA) and sequence related amplified polymorphism (SRAP)-BSA analysis, the nearest linkage marker is 2.5 cM apart from the RsrR gene. The gene RsrR has been transferred into two elite maize inbred lines, ‘Huangzao4’ and ‘Qi319’, through traditional hybridization and marker assisted selection. The converted lines can be used in maize MHS-resistance breeding.

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Trends of grain yield and plant traits in Chinese maize cultivars from the 1950s to the 2000s - Xiaoke Ci; Mingshun Li; Jiashun Xu; Zhenyu Lu; Pengfei Bai; Gaolin Ru; Xiaoling Liang; Degui Zhang; Xinhai Li; Li Bai; Chuanxiao Xie; Zhuanfang Hao; et al. (Euphytica, 2012)

Polymorphism of vascular endothelial growth factor −1154G>A (rs1570360) with cancer risk: a meta-analysis of 16 case–control studies - Ting-Ting Hong; Ru-Xia Zhang; Xiao-Hong Wu; Dong Hua (Molecular Biology Reports, 2012)

Increased function of the TRPV1 channel in small sensory neurons after local inflammation or in vitro exposure to the pro-inflammatory cytokine GRO/KC - Fei Dong; Yi-Ru Du; Wenrui Xie; Judith A. Strong; Xi-Jing He; Jun-Ming Zhang (Neuroscience Bulletin, 2012)

Effect of heavy metal-solubilizing microorganisms on zinc and cadmium extractions from heavy metal contaminated soil with Tricholoma lobynsis - Ling-yun Ji; Wei-wei Zhang; Dong Yu; Yan-ru Cao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Antioxidant effect of a phytoestrogen equol on cultured muscle cells of embryonic broilers - Xiao-Jing Wei; Jing Wu; Ying-Dong Ni; Li-Zhi Lu; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Study of prestack elastic parameter consistency inversion methods - Han-Dong Huang; Ru-Wei Zhang; Guo-Qiang Shen; Fei Guo; Jia-Bei Wang (Applied Geophysics, 2011)

Effect of glucocorticoids pretreatment on steroidogenic capacity of adrenocortical cells isolated from Meishan piglets - Liu-An Li; Zhan-Wang Wu; Xiao-Jing Yang; Ying-Dong Ni; Nahid Parvizi; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Expression of tyrosine kinase receptor C in the segments of the spinal cord and the cerebral cortex after cord transection in adult rats - Dong-Xiang Qian; Hong-Tian Zhang; Ying-Qian Cai; Peng Luo; Ru-Xiang Xu (Neuroscience Bulletin, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Genetic Analysis and Molecular Mapping of a Novel Gene Conferring Resistance to Rice Stripe Virus - Feng Zhao; Zhijun Cai; Tiezhu Hu; Haigen Yao; Li Wang; Na Dong; Bin Wang; Zhengang Ru; Wenxue Zhai (Plant Molecular Biology Reporter, 2010)

The Gab2 in signal transduction and its potential role in the pathogenesis of Alzheimer’s disease - Xiao-Ling Pan; Ru-Jing Ren; Gang Wang; Hui-Dong Tang; Sheng-Di Chen (Neuroscience Bulletin, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Use of simple sequence repeats for authentication of sugarcane hybrids generated from Yunnan Erianthus rockii - Yan-Fen Jing; Lian-an Tao; Xin-long Liu; Ru-dong An; Xue-kuan Chen (Sugar Tech, 2009)

High frequency plant regeneration following abnormal shoot organogenesis in the medicinal tree Hovenia dulcis - Mi Jin Jeong; Hyun Jin Song; Dong Jin Park; Ji Yun Min; Jin Seong Jo; Bo Min Kim; Hak Gon Kim; Yong Duck Kim; Ru Mi Kim; Chandrakant S. Karigar; Myung Suk Choi (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Phthalic Acid Induces Oxidative Stress and Alters the Activity of Some Antioxidant Enzymes in Roots of Malus prunifolia - Ru Bai; Fengwang Ma; Dong Liang; Xin Zhao (Journal of Chemical Ecology, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Sorption of methyl-parathion and carbaryl by an organo-bentonite - Qing-ru Zeng; Bo-han Liao; Bo Yang; Hong-xiao Tang; Nan-dong Xue (Biology and Fertility of Soils, 2006)

Sustainable development of marine economy in China - Yao-guang Zhang; Li-jing Dong; Jun Yang; Sheng-yun Wang; Xin-ru Song (Chinese Geographical Science, 2004)